Broadband graphene-based photoacoustic microscopy with high sensitivity. Issue 18 (26th April 2018) - Yang, Fan; Song, Wei; Zhang, Chonglei; Min, Changjun; Fang, Hui; Du, Luping; Wu, Peng; Zheng, Wei; Li, Changhui; Zhu, Siwei; Yuan, Xiaocong
Abstract : High-sensitivity and broadband graphene-based detector for in vivo photoacoustic microscopy. Abstract : Photoacoustic microscopy (PAM) enables the measurement of properties associated with optical absorption within tissues and complements sophisticated technologies employing optical microscopy. An inadequate frequency response as determined by a piezoelectric ultrasonic transducer results, however, in poor depth resolution and inaccurate measurements of the coefficients of optical absorption. We developed a PAM system configured as an attenuated total reflectance sensor with a ten-layer graphene film sandwiched between a prism and water (the coupling medium) for photoacoustic (PA) wave detection. Transients of the PA pressure cause perturbations in the refractive index of the water thereby changing the polarization-dependent absorption of the graphene film. The signal in PA detection involves recording the difference in the temporal-varying reflectance intensity between the two orthogonally polarized probe beams. The graphene-based sensor has an estimated noise-equivalent-pressure sensitivity of ∼550 Pa over an approximately linear pressure response from 11.0 kPa to 55.0 kPa. Moreover, it enables a much broader PA bandwidth detection of up to ∼150 MHz, primarily dominated by a highly localized evanescent field. From the strong optical absorption of inherent hemoglobin, in vivo label-free PAM imaging provided a three-dimensional viewing of the microvasculature of a mouse ear. These results suggest great potential for graphene-based PAM in biomedical investigations, such as microcirculation studies.